Measurement of Evapotranspiration in Turfgrass: Recommended Techniques and Adjustment Coefficients - Kenton W. Peterson; D. Bremer; Kira B. Shonkwiler; J. M. Ham (Kansas Agricultural Experiment Station Research Reports, 2017)
Evapotranspiration (ET) from turfgrass can be measured directly using lysimeters (LYS), estimated from weather data using models, or approximated using atmometers. Evapotranspiration measurements from LYS were compared with ET estimates from four variations of the American Society of Civil Engineers (ASCE) standardized ET equation including the use of: 1) hourly steps of measured net radiation (Rn) (ASCEHM); 2) hourly steps of Rncalculated from global irradiance (ASCEHC); 3) daily steps of measured Rn(ASCEDM); and 4) daily steps of Rncalculated from global irradiance (ASCEDC); ET from LYS was also compared with the Priestley-Taylor (PT) model and atmometers. All collections were from a sward of tall fescue (Schedonorus arundinaceusSchreb.) turfgrass at the Rocky Ford Turfgrass Research Center, Manhattan, KS. Results indicate the ASCEDCcould improve irrigation scheduling in turfgrass by providing accurate ET estimates from standard weather station data where measured Rnis not available. Adjustment factors for several of the methods are recommended below.
Keywords: Evapotranspiration; evapotranspiration models; water; tall fescue